1990
DOI: 10.1590/s0102-311x1990000200006
|View full text |Cite
|
Sign up to set email alerts
|

Fatores envolvidos na reatividade do PPD em pacientes com doença de Hansen

Abstract: INTRODUÇÃOHá evidências de que a resistência à infecção pelo microorganismo intracelular Mycobacterium leprae requer uma eficaz resposta imune mediada por células. Os aspectos clínicos e a evolução da Hanseníase dependem da extensão desta resposta ao microorganismo que, por sua vez, controla a multiplicação bacilar (14).No pólo tuberculóide, onde se observa uma evidente imunidade celular, o crescimento bacteriano e a disseminação são controlados. No pólo lepromatoso, onde pouca ou nenhuma imunidade celular est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Other retrospective studies on the same cohort as that covered in the present study also revealed variations in the findings regarding the protective effect of BCG [8, 21]. However, the methodological differences (sampling, analysis methods, and follow-up time) of these studies must not be ignored.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Other retrospective studies on the same cohort as that covered in the present study also revealed variations in the findings regarding the protective effect of BCG [8, 21]. However, the methodological differences (sampling, analysis methods, and follow-up time) of these studies must not be ignored.…”
Section: Discussionmentioning
confidence: 49%
“…Matos et al (1999) found a protective effect of 62% among household contacts after adjustments via the Mitsuda test and the clinical form of the index case [8]. Duppre et al (1998) showed the protective effect of a childhood BCG scar in the contacts of multibacillary (MB) index cases [21]. …”
Section: Discussionmentioning
confidence: 99%